Bivalve Community Structure in Coastal Water of Lalang Village, Siak District Riau Province - Ritonga, Rifai Ramadhan; Zulkifli, Zulkifli; Nasution, Syafruddin (Journal of Coastal and Ocean Sciences, 2023)
This research was conducted in July - September 2022 in the coastal waters of Lalang Village, Sungai Apit District. The purpose of this study was to determine the structure of the bivalve community including abundance, relative abundance, diversity, uniformity index, dominance index, and distribution pattern. Sampling was done using the line transect method at 3 stations. The results of the study obtained two species of bivalves in the waters of Lalang Village Beach, namely Polymesoda erosa and Glauconome virens with abundance at all stations ranging from 1.67 - 5.33 ind/m2. The bivalve diversity index value at the study site is categorized as low diversity. The bivalve uniformity index value is high, and the dominance index value indicates the presence of dominating species. The distribution pattern of bivalves between observation stations is clustered